Hypnosis-based psychodynamic treatment in ALS: a longitudinal study on patients and their caregivers - Kleinbub, Johann R.; Palmieri, Arianna; Broggio, Alice; Pagnini, Francesco; Benelli, Enrico; Sambin, Marco; Sorarù, Gianni (Frontiers in Psychology, 2015)
Background: Evidence of psychological treatment efficacy is strongly needed in ALS, particularly regarding long-term effects. Methods: Fifteen patients participated in a hypnosis treatment and self-hypnosis training protocol after an in-depth psychological and neurological evaluation. Patients’ primary caregivers and 15 one-by-one matched control patients were considered in the study. Measurements of anxiety, depression and quality of life were collected at the baseline, post-treatment, and after 3 and 6 months from the intervention. Bayesian linear mixed-models were used to evaluate the impact of treatment and defense style on patients’ anxiety, depression, quality of life, and functional impairment (ALSFRS-r), as well as on caregivers’ anxiety and depression. Results: The statistical analyses revealed an improvement in psychological variables’ scores immediately after the treatment. Amelioration in patients’ and caregivers’ anxiety as well as caregivers’ depression, were found to persist at 3 and 6 months follow-ups. The observed massive use of primitive defense mechanisms was found to have a reliable and constant buffer effect on psychopathological symptoms in both patients and caregivers. Notably, treated patients decline in ALSFRS-r score was observed to be slower than that of control group’s patients. Discussion: Our brief psychodynamic hypnosis-based treatment showed efficacy both at psychological and physical levels in patients with ALS, and was indirectly associated to long-lasting benefits in caregivers. The implications of peculiar psychodynamic factors and mind-body techniques are discussed. Future directions should be oriented toward a convergence of our results and further psychological interventions, in order to delineate clinical best practices for ALS.